Impact of reduced tillage on CO2 emission from soil under maize cultivation - Rutkowska, Beata; Szulc, Wiesław; Sosulski, Tomasz; Skowrońska, Monika; Szczepaniak, Jan (Soil & tillage research, 2018)
•The impact of a new environmentally safe and low-cost maize production system on corn yield and soil CO2 emission was evaluated.•Maize grain yield was more determined by weather and soil condition than by tillage system.•The CO2 emission was significantly higher in the conventional system than under new maize production system.•The higher CO2 emission was observed in a year with greater amount of rainfall. Carbon dioxide is an important greenhouse gas, which is released through human activities such as deforestation, burning fossil fuels, agriculture, and degradation of soil. The type of soil tillage systems has a very important impact on soil CO2 emissions. Usually higher soil CO2 emission have been observed under conventional tillage compared to reduced tillage. Maize is one of the main cereals grown around the world that reacts positively on conservation tillage. We hypothesized that reduced tillage with sub-soil fertilizer application could increase maize yield and reduce carbon emissions compared to conventional plowing. Therefore we studied CO2 emissions from soil under a conventional and innovative, environmentally safe, low-cost maize production system dedicated both to reduce time and resources and to manage the field sustainably with a lower CO2 footprint. We observed that the magnitude of grain yield depended on soil and climate conditions but not on the cultivation system. The CO2 emission level depended on the year of the study and the soil tillage method and was subject to considerable changes during the growing season. The use of reduced soil tillage significantly limited emissions of the analyzed gas into the atmosphere. Depending on the year of the study, CO2 emissions in the reduced tillage system were 7 to 35% lower than those in the conventional system. The extent of the reduction in CO2 emissions achieved under reduced tillage is very large relative to conventional tillage, which is probably due to the relatively low organic matter content of the both investigated soils in the conventional tillage. We could show that on sandy soils with a low organic matter content reduction in tillage is a factor significantly diminishing CO2 emissions.